DRIVING IMMUNIZATION: INNOVATIVE APPROACHES TO COVID-19 VACCINATION ON COLLEGE CAMPUSES - Chege, Wanjiku Muthoni; Mwamba, Kaleb Chola (International Research Journal Diagnostics, 2024)
The impact of COVID-19, three years postpandemic declaration, remains significant, with global efforts focused on vaccination as a key strategy for mitigation. The rapid development and distribution of vaccines have become essential in the fight against the virus. However, vaccine acceptance among the public is influenced by a myriad of factors, including cultural, religious, economic, and geopolitical considerations. This phenomenon, known as vaccine hesitancy, poses a challenge to achieving widespread immunization. Addressing vaccine hesitancy is crucial in maintaining public health and achieving herd immunity. This article explores the multifaceted nature of vaccine hesitancy and highlights the importance of understanding and addressing the underlying reasons for vaccine reluctance.